PELAKSANAAN AKTA SEBAGAI PENGAKUAN HUTANG DALAM PERJANJIAN KREDIT PADA BANK PEMBANGUNAN DAERAH (BPD) SAMARINDA - Leo Josten Siregar (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTIn implementation or implementation it is not easy to determine whether the proposed grosse certificate has met both formal and material requirements. Especially regarding the material requirements of the grosse deed. In practice many cause problems because of the development in msayarakat the existence of grosse deed based on credit agreement from the bank as the principal agreement. Grosse deed of debt acknowledgment with other agreements in the form of power of sale and / or power of attorney and others in a grosse certificate is not allowed because it causes rijinya in executing execution, that is whether execution is executed to grosse deed of recognition of debt or to certificate of mortgage . So that this violates the rule of law as regulated in article 224 HIR and fatwa MA. 213/229/85 / UM-TU / Pdt dated April 16, 1985 so that grosse aktapakuan debt is not purely recognition of debtors debtors to a certain amount of creditors and cause grosse deed of recognition of the debt is null and void execution implementation can not be implemented. And concerning repayment of interest, fines and penalties and other expenses for the execution expenses incurred in a grosse deed of debt acknowledgment can not be justified in accordance with the nature of the grosse deed which must be purely a one-sided statement from the debtor who admits to owe a certain sum to the creditor with the rules of article 224 HIR and the fatwa of MA no. 213/229/85 / UM-TU / Pdt dated April 16, 1985, while the clause on payment of installments, interest and penalties and other expenses for execution fee should be included in the credit agreement deed only. The procedure for grosse execution of a debt acknowledgment does not have to go through the Court of Justice, but in practice it is the case that the application for a debt recognition grosse must pass through the court process first and can not be directly executed by the execution of the debt recognition grosse and this takes a long time. While the government bank of Bank Rakyat Indonesia East Kutai Branch will be submitted to KP2LN and PUPN, although if the institution filed a civil suit to the District Court then the Court should not refuse on the grounds not the authority of the Court.